Permasalahan Pencapaian Kompetensi Dasar Pengetahuan dan Keterampilan Siswa Kelas V dalam Pembelajaran Fiqih pada Materi Tata Cara Haji - Nur Sholihah, Siti; Umkabu, Talabudin; Rokhmah, Siti; Al Jauhari, Shofwan (CV. Creative Tugu Pena, 2024)
The purpose of this research is to find out how fiqh learning of Hajj procedures, the achievement of basic competencies of knowledge and skills and the problems and efforts of educators and madrasah in achieving basic competencies of knowledge and skills of students' Hajj procedures. The research method is descriptive qualitative using methodological and pedagogical approaches. The data collection technique is through observation, interviews and document studies, the subject of research on learning the procedures of Hajj, achieving the competencies of knowledge and skills of Hajj procedures, influencing factors and efforts of teachers and madrasah in overcoming the problems of Hajj procedures with the object of research students, educators and madrasah head. The data analysis uses Miles and Huberman by reducing data, presenting data and verifying or drawing conclusions. The results of this study are the learning process of fiqh procedures for Hajj is in accordance with the applicable curriculum, namely through planning, implementation, and assessment of learning. Achievement of knowledge is done through classroom learning with lecture and discussion methods, measuring the achievement of knowledge competency results through daily tests and homework assignments with the results of 73% who completed KKM from 22 students. While the achievement of skills is taught through practice and student projects with 55% KKM completeness. Learners who have not completed the KKM are then remedied with Keywords: Achievement of Basic Competencies, Larning Fiqh, Basic Competencies Knowledge and Skills